Analisis Dan Perancangan Sistem Informasi Presensi Berbasis Gps Dan Foto: Studi Kasus PT Sakura Anugrah Pratama - Azam Fathurrahman; Karno Diantoro; Adi Wahyu Setiawan (Journal of Innovative and Creativity (Joecy), 2026)
Presence is a metric used to measure employee performance. PT Sakura Anugrah Pratama faces challenges in using fingerprint machines for employee attendance management. The current problems include difficulties in real-time attendance monitoring, inability to monitor branch office employees from the head office, and challenges in processing data obtained from fingerprint devices according to company standards. This research aims to design a location-based attendance information system using GPS and photo technology. The system was developed using the Rapid Application Development (RAD) methodology with PHP programming language using the Laravel framework and MySQL database. The proposed system enables real-time attendance tracking, provides photo evidence for verification, and generates standardized reports automatically. The implementation results show that the GPS and photo-based attendance information system successfully addresses attendance management issues at PT Sakura Anugrah Pratama by presenting real-time, accurate, and standardized data. Blackbox testing confirmed that all system functions operate according to specifications, with 100% success rate for core features including GPS-based check-in, photo verification, and automated reporting.